EFFECT OF ACCOUNTING PROGRAM DEVELOPMENT BANK STATEMENT OF FINANCIAL ACCOUNTING STANDARDS BASED ON THE FINANCIAL DISTRICT IN BMT TEGAL - Mulyani, Sumarno; ., Mulyanto (PERMANA, 2012)
The purpose of this study to analyze the effect of bank accounting program for the preparation of financial statements in financial accounting standards in BMT Tegal regency. The hypothesis in this study is thought to affect the use of banking accounting program for the preparation of financial statements in financial accounting standards in BMT Tegal regency. Its population is on the BMT Tegal regency Employee Data collection methods used questionnaires.. Data analysis methods used in this research that analyzes the correlation coefficient rank spearman, coefficient of determination analysis and hypothesis testing of correlation coefficient rank spearman. From the calculation results obtained values ​​of r s = 0.54 which means there is a strong and positive relationship between banking accounting program with the preparation of financial statements in BMT in Tegal regency.. Analysis of Determination with the calculated r 2 = 54.5%, it was known whether or not the preparation of financial statements is affected by BMT Tegal regency, while the remaining 45.5% (49.59%) is derived from the influence of other variables are undefined... Keywords: Program, Finance